From the other side of the world extraordinary entrepreneurs, unlikely places - Bayrasli, Elmira (New York PublicAffairs, 2015)
Elmira Bayrasli's worldview was turned upside down when a woman in Bosnia told her, "thanks for the help. But we need work and jobs, not foreign aid." That prompted Bayrasli to embark on a worldwide quest to find how talented people have overcome insurmountable obstacles to build high-growth businesses that are driving wealth and building communities, regions and countries. Through seven remarkable stories, Elmira Bayrasli shows why the next Steve Jobs and the next Apple, Google or Facebook is as likely to come from Nigeria, Pakistan or Mexico as Silicon Valley. She discovers that what distinguishes techies in Silicon Valley from women selling bamboo stools in Bangladesh isn't their sophistication but simply the conditions that are necessary to sustain and scale business ideas. In the absence of these obstacles, global entrepreneurship can flourish. Bayrasli paints compelling stories of extraordinary entrepreneurs creatively battling corruption, lack of infrastructure, capital shortages and underdeveloped supplier and customer networks. She offers solutions that can be utilized by entrepreneurs everywhere, and shows why micro-finance, social entrepreneurship, and foreign aid are not enough. Most importantly, she shows how the key to building successful entrepreneurial ecosystems is to provide the framework that enables start-ups to scale.
Includes bibliographical references and index.
Keywords: New business enterprises